Relationship Between Wood Specific Gravity and Average Annual Ring Width of 15 Korean Wood Species - Kug-Bo Shim; Min-Soon Park; Yonggun Park; Chul-Ki Kim; Hyun Mi Lee (BioResources)
The correlation between specific gravity and average annual ring width was studied for 15 major Korean tree species. In coniferous trees, species with narrower rings exhibited higher specific gravity, with strong correlations observed in Pinus densiflora (Gangwon), Larix kaempferi, and Pinus rigida. In deciduous trees, the correlation between specific gravity and annual ring width did not exhibit a consistent pattern based on the distinction between diffuse-porous and ring-porous species. The correlation of Liriodendron tulipifera (diffuse-porous species) and Quercus mongolica (ring-porous species) showed higher specific gravity with wider rings, whereas other species, such as Betula platyphylla (diffuse-porous species) and Robinia pseudoacacia (ring-porous species) exhibited the opposite trend. Therefore, the correlation in deciduous trees appears to be an inherent characteristic of each species rather than a result of porous type.